Kerja Sama Perpustakaan Berbasis Digital: Membangun Akses dan Kolaborasi untuk Pendidikan dan Inovasi - Harahap, Yana Annur; Lubis, Sopian; Azhar, Khairul; Ginting, Suasana Nikmat; Hasibuan, Mulkan (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2023)
This study discusses forms of cooperation between domestic libraries and foreign libraries that aim to exchange information and expand collection materials and improve collection services to users so that the insights of visitors who come and access libraries that have collaborated are broader and gain a lot of experience. Methods of data collection using literature (print and non-print). The data obtained is then arranged or classified, analyzed, and interpreted. The results of the study concluded: 1) The forms of library collaboration that can be carried out are: (a) sharing digital collections through a platform that can be accessed by all libraries involved in the collaboration, (b) collaboration in creating and managing joint databases to expand reach and enriching library collections, as well as facilitating access for users to find the information needed, (c) library cooperation in the development of digital technology and infrastructure. 2) The steps for building digital-based library collaboration are as follows: (a) identify libraries that wish to work together, (b) determine the goals and benefits of collaboration, (c) form a work team, (d) discuss and determine standards, (e) infrastructure and system development, (f) collection development and management, (g) monitoring and evaluation.